Inhibition of RAD51 by siRNA and Resveratrol Sensitizes Cancer Stem Cells Derived from HeLa Cell Cultures to Apoptosis - Graciela Ruíz; Heriberto A. Valencia-González; Ismael León-Galicia; Enrique García-Villa; Alejandro García-Carrancá; Patricio Gariglio (Stem Cells International)
Cervical cancer is the second most frequent tumor type in women worldwide with cases developing clinical recurrence, metastasis, and chemoresistance. The cancer stem cells (CSC) may be implicated in tumor resistance to therapy. RESveratrol (RES), a natural compound, is an antioxidant with multiple beneficial activities. We previously determined that the expression of RAD51 is decreased by RES. The aim of our study was to examine molecular mechanism by which CSC from HeLa cultures exhibit chemoresistance. We hypothesized CSC repair more efficiently DNA breaks and that RAD51 plays an important role in this mechanism. We found that CSC, derived from cervical cancer cell lines, overexpress RAD51 and are less sensitive to Etoposide (VP16). We inhibited RAD51 in CSC-enriched cultures using RES or siRNA against RAD51 messenger RNA and observed a decrease in cell viability and induction of apoptosis when treated simultaneously with VP16. In addition, we found that inhibition of RAD51 expression using RES also sensitizes CSC to VP16 treatment. Our results suggest that resveratrol is effective to sensitize cervical CSC because of RAD51 inhibition, targeting high RAD51 expressing CD49f-positive cells, which supports the possible therapeutic application of RES as a novel agent to treat cancer.